Efek Pemberian Asam Alfa Lipoat pada Histopatologi Aorta Torakalis Tikus Diabetes Melitus Tipe 2 - Rijalun Arridho; Ismawati Ismawati; Enikarmila Asni; Ilhami Romus (Jurnal Ilmu Kedokteran, 2020)
Atherosclerosis is arterial wall’s disease initiated by lipid retention, oxidation, and modification, provoking chronic inflmmation ultimately causing stenosis and thrombosis. This study investigated the effect of alpha lipoic acid (ALA) on thoracic aorta type 2 diabetic rat. Fifteen adult male rat of Rattus novergicus Wistar strain were separated into three groups (n=5), there were labelled as control, type 2 diabetes (DM), and DM + ALA. Type 2 diabetic rats were induced by streptozotocin (50 mg/kg bodyweight) and nicotinamide (110 mg/kg bodyweight) and categorized as diabetic rat if blood glucose level >250 mg/dl. Alpha lipoic acid was administered via intraperitoneal (60 mg/kg/day) and conducted for 3 weeks. The measured parameter was atherosclerosis lesion score. Results showed that there was no significant difference in atherosclerosis lesion scores between all groups designed (p=0,071). It can be concluded that ALA did not have a significant effect on atherosclerosis lesion of thoracic aorta type 2 diabetic rat.